An End User Development Approach for Mobile Web Augmentation - Bosetti, Gabriela Alejandra (2017)
The trend towards mobile devices usage has made it possible for theWeb to be conceived not only as an information space but also as a ubiquitous platformwhere users performall kinds of tasks. In some cases, users access theWeb with nativemobile applications developed for well-known sites, such as, LinkedIn, Facebook, and Twitter. These native applications might offer further (e.g., location-based) functionalities to their users in comparison with their correspondingWeb sites because they were developed with mobile features in mind. However, many Web applications have no native counterpart and users access them using a mobileWeb browser. Although the access to context information is not a complex issue nowadays, not all Web applications adapt themselves according to it or diversely improve the user experience by listening to a wide range of sensors. At some point, users might want to add mobile features to these Web sites, even if those features were not originally supported. In this paper, we present a novel approach to allow end users to augment their preferred Web sites with mobile features. We support our claims by presenting a framework for mobileWeb augmentation, an authoring tool, and an evaluation with 21 end users.